PENCEGAHAN BULLYING TERHADAP ANAK MELALUI PENGUATAN NILAI-NILAI KEISLAMAN DI DESA SOKARAJA KULON, KECAMATAN SOKARAJA, KABUPATEN BANYUMAS - Yuliani Catur Rini; Kartika Winkar Setya; Ari Tri Wibowo (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Nowadays there are rampant acts of bullying perpetrated by children with child victims both at school and in friendship circles at home. Bullying is a trend that is rife among young people as an action that is considered normal, contemporary and an ordinary joke, even though the consequences are quite dangerous, some cases result in physical injury to the victim, others become depressed and stressed, even victims of bullying who hold grudges can commit irrational actions as an outpouring of frustration such as shooting bullies, setting fire to schools where victims are often bullied and so on which end in criminal proceedings Muslimat as an autonomous body (Banom) under the auspices of the Nahdlatul Ulama (NU) organization plays an important role in providing education and knowledge to society in general and members in particular consisting of mothers who incidentally are the main pillars of the family. Muslimat Twig Sokaraja Kulon Village feels the need to equip its members, all of whom are mothers, with knowledge about bullying to prevent their children, siblings and even their grandchildren from being bullied. The implementation of PKM uses a comprehensive group-based legal counseling method and local wisdom. Team activities are carried out in a measurable manner through the achievement of targets and the resulting outputs, including increasing partners' knowledge of PKM material. The result of this PKM is to increase the knowledge and awareness of the community in general and partners in particular regarding bullying and its prevention through instilling Islamic values. It is hoped that the knowledge possessed by partners can become the basis for partners to disseminate their knowledge to the wider community to reduce bullying cases.